Padrão de especialização e saldo comercial da China com Estados Unidos, Europa e Ásia no início do Século XXI - Miranda, Maria Inês Cunha (2013)
The rise of China has been providing various effects on developed and developing countries, particularly its Asian neighbors which compete in third markets, such as the U.S., Europe and Japan this sense, the present study aimed to analyze the pattern of Chinese trade with two different groups of countries: the Asian neighbors (Asian Tigers and Dragons) and developed countries (United States, Europe and Japan) during the 2000s. To this end, this paper adopts the methodology of second breakdown of trade technological intensity proposed by Lall (2000). Furthermore, to analyze the intensity of trade between these economies as well as potential threats over their Chinese business partners close, we calculated the following indicators of trade: Trade Intensity Index (TII), Trade Orientation Index (TOI) , Intra-Industry Trade Index (ICII), Index Of Revealed Comparative Advantage (RCA), and, finally, the Contribution To The Balance Index (ICS). The main result achieved is the existence of China\'s trade patterns differ for each group of countries, according to the type of expertise of each partner.